(untitled) (Indonesian Journal of Agrarian Law, 2026)
This research analyzes the legal certainty of Tegal Pangonan land physically occupied by the community, using a case study of land tenure dynamics in Meteseh Village, Kendal Regency. The primary focus of this study is to examine the phenomenon where long-term physical occupation of land has not yet received formal legal recognition through certification. The research problem stems from differing interpretations of administrative procedures at the village level, which have hindered the land registration process. This study aims to analyze the agrarian legal framework in resolving Tegal Pangonan land tenure conflicts and to identify the role of local government agencies in the land administration process. The method employed is socio-legal (juridical-empirical) with a descriptive-analytical approach. The findings indicate that the lack of legal certainty is often caused by inconsistencies in land data and differing interpretations of evidence regarding physical occupation. As a conceptual solution, this research emphasizes the importance of effective mediation and policy synchronization between village governments, land agencies, and the state to achieve agrarian justice for the community.